Online Home Sales Technology Development - B J Muhammad; L Warlina (Peneliti.net, 2020)
This study aims is to determine the extent of online home sale business can be developed. The online business recently is accessible among communities all over the world. Therefore, the online home sales business can facilitate the community to save more time efficiently. This study used a competitive website analysis method to find out the development of online home sales. The results of this research will analyze several online home sale business in Indonesia. The support of technological progress in the current era will make online home sales business a promising future.